Songs of Resistance: Subaltern Voices and Digital Solidarity from Pramoedya Ananta Toer to Band Sukatani - Remalya Sidjabat, Yedija (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
This paper explores subaltern representation and digital solidarity, connecting literary resistance in Pramoedya Ananta Toer’s works with contemporary digital expressions, exemplified by Band Sukatani’s protest song. It addresses how Pramoedya’s narratives of subaltern struggles resonate in modern digital contexts. Utilizing textual analysis of selected Pramoedya novels, content analysis of Sukatani’s lyrics, and online discourse analysis, this study applies theories from subaltern studies, nationalism and identity, and digital affect to examine persistent issues of censorship, institutional oppression, and mobilization of digital solidarity. Findings demonstrate continuity in forms of resistance from literary to musical and digital platforms, highlighting the enduring relevance of Pramoedya’s works and contemporary activism through digital media. The study concludes that subaltern resistance remains dynamic and robust, reinforced by digital cultural expressions that sustain and amplify the legacy of Pramoedya Ananta Toer.